Sex-dependent effect of perinatal hypoxia on cardiac tolerance to oxygen deprivation in adults - Ostadal, B; Ostadalova, I; Szarszoi, O; Netuka, I; Olejnickova, V; Hlavackova, M (Canadian journal of physiology and pharmacology, 2021)
Epidemiological studies have demonstrated a relationship between the adverse influence of perinatal development and increased risk of ischemic heart disease in adults. From negative factors to which the fetus is subjected, the most important is hypoxia. The fetus may experience hypoxic stress under different conditions, including pregnancy at high altitude, pregnancy with anemia, placental insufficiency, and heart, lung, and kidney disease. One of the most common insults during the early stages of postnatal development is hypoxemia due to congenital cyanotic heart defects. Experimental studies have demonstrated a link between early hypoxia and increased risk of ischemia/reperfusion injury (I/R) in adults. Furthermore, it has been observed that late myocardial effects of chronic hypoxia, experienced in early life, may be sex-dependent. Unlike in males, perinatal hypoxia significantly increased cardiac tolerance to acute I/R injury in adult females, expressed as decreased infarct size and lower incidence of ischemic arrhythmias. It was suggested that early hypoxia may result in sex-dependent programming of specific genes in the offspring with the consequence of increased cardiac susceptibility to I/R injury in adult males. These results would have important clinical implications, since cardiac sensitivity to oxygen deprivation in adult patients may be significantly influenced by perinatal hypoxia in a sex-dependent manner.
Keywords: hypoxie plodu; heart; perinatal hypoxia; těhotenství; cœur; sex differences; Fetal Hypoxia; sexuální faktory; mužské pohlaví; Myocardial Reperfusion Injury; Myocardial Ischemia; ischemia/reperfusion injury; Adult; reperfuzní poškození myokardu; kyslík; ženské pohlaví; Humans; Pregnancy; Sex Factors; zpožděný efekt prenatální expozice; différences entre les sexes; lésions d’ischémie/reperfusion; Heart; rizikové faktory; ischemická choroba srdeční; Oxygen; dospělí; Female; Risk Factors; hypoxie périnatale; Prenatal Exposure Delayed Effects; srdce; lidé; Male